1998
DOI: 10.1021/ic971579d
|View full text |Cite
|
Sign up to set email alerts
|

Helical Silver(I)−2,4‘-Bipyridine Chains Organized into 2-D Networks by Metal−Counterion or Metal−Metal Bonding. Structures of [Ag(2,4‘-bipyridine)]X (X- = NO3- or ClO4-)

Abstract: Two compounds, [Ag(2,4‘-bpy)]NO3 (1) and [Ag(2,4‘-bpy)]ClO4 (2), were obtained from self-assembly of AgX (X = NO3 -, ClO4 -) with 2,4‘-bipyridine (2,4‘-bpy). 1 crystallizes in the orthorhombic space group Pbca, with a = 11.2884(7) Å, b = 11.3981(10) Å, c = 16.5299(13) Å, and Z = 8, while 2 crystallizes in the monoclinic space group P21 /c, with a = 10.6361(4) Å, b = 9.9896(4) Å, c = 11.2661(6) Å, β = 98.527(4)°, and Z = 4. Both complexes consist of helical [Ag(2,4‘-bpy)]∞ chains that are surrounded by nitrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 191 publications
(53 citation statements)
references
References 39 publications
5
44
0
4
Order By: Relevance
“…The competition between cyclic species and open-chain oligomers or polymers has been observed in many related systems. As outlined by Fujita, in studying the self-assembly of 15.897 (1) 11.962 (4) 7.430 (5) 8.298 (1) 17.100 (3) 11.555 (5) c/A Ê 10.228 (4) 13.595 (1) 14.509 (4) 14.478 (1) 13.890 (1) 14.220 (6) 20.424 ( 2291.8 (19) 3181.5 (7) 4726.7 (18) 1911.5(13) [(en)Pd(NO 3 ) 2 ] with pyridine-based bridging ligands, systems under kinetic control disfavour cyclization, while thermodynamic conditions facilitate the formation of macrocycles, due to signi®cant entropy effects that favour small cyclic structures over polymeric structures. 6d Cyclization was, therefore, observed to occur more readily in the presence of more labile metal±ligand bonds, at low reagent concentrations and at higher temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The competition between cyclic species and open-chain oligomers or polymers has been observed in many related systems. As outlined by Fujita, in studying the self-assembly of 15.897 (1) 11.962 (4) 7.430 (5) 8.298 (1) 17.100 (3) 11.555 (5) c/A Ê 10.228 (4) 13.595 (1) 14.509 (4) 14.478 (1) 13.890 (1) 14.220 (6) 20.424 ( 2291.8 (19) 3181.5 (7) 4726.7 (18) 1911.5(13) [(en)Pd(NO 3 ) 2 ] with pyridine-based bridging ligands, systems under kinetic control disfavour cyclization, while thermodynamic conditions facilitate the formation of macrocycles, due to signi®cant entropy effects that favour small cyclic structures over polymeric structures. 6d Cyclization was, therefore, observed to occur more readily in the presence of more labile metal±ligand bonds, at low reagent concentrations and at higher temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…The 2,4'-bipy ligand is able to act as exo-bidentate with digonal metals as Ag(I), generating chains. 19 With 1, therefore, the only suitable coordination positions could be the two trans axial, but the weakness of the interactions along these directions leads to a different product. Noteworthy the mononuclear complexes are joined into one-dimensional chains (see Fig.…”
Section: Discrete Molecular Architecturesmentioning
confidence: 99%
“…The nitrates involved in the metal bonding in these complexes show three variations: the nitrate may bind one oxygen to one silver [8], two oxygen to one silver [9,13], or two oxygen on one nitrate group may bridge two silvers on separate molecules [7]. The silver geometry is either linear or bent with the perturbation to non-linear geometries caused by the cation-anion interaction.…”
Section: 2mentioning
confidence: 99%
“…Preliminary observations have shown that weakly coordinating anions such as tend to be located near the silver [6,10]. However, several structures have seen nitrate-silver interactions that lead to: monodentate O-Ag bonding [8]; bidentate nonbridging O-Ag bonding [9,13]; and bidentate bridging bonding [7]. In Ag(1) 2 NO 3 , one nitrito group oxygen is within bonding distance to the silver at a distance of 2.461 (5) Å with the other at a distance of over 3 Å.…”
Section: Nitrate Coordination To Silvermentioning
confidence: 99%
See 1 more Smart Citation